A CRITICAL REVIEW ON HRIDYA (CARDIOTONIC) ACTION OF DADIM (PUNICA GRANATUM LINN.) WITH SPECIAL REFERENCE TO AYURVEDIC AND MODERN ASPECT (International Journal of Ayurveda and Pharma Research, 2018)
Cardiovascular diseases pose an alarming threat to global health. Heart disease is still the leading cause of death in India, Killing 1.7 million Indians in 2016. According to Ayurved, Hriday or Heart is a vital organ as any type of damage to this organ leads to loss of life. Hridya mahakashaya (group of cardiotonic drugs i.e. drugs having beneficial action on the heart) possessing sour taste has been explained in Charak Samhita. These drugs are useful in maintaining cardiac health and also mental health. Dadim (Punica granatum Linn.) means Pomegranate is one of the Dravyas explained under Hridya group. By means of its virtues, Dadim performs Agnideepan, Rasa-Dhatwagnideepan, Pittashamana, Vatanuloman and the Hridya function; and strengthens heart moreover nourishes brain. Hriday is one of the sites for Mana (psyche). Amla rasa of Dadim performs Tarpana karma of Hriday, satiates mind and improves mental strength. In this review the antioxidant, anti-inflammatory, anti- hypertensive, Anti-stress, thrombolytic, anxiolytic and anti-depressant actions of Dadim have been focused which are the key factors in treatment of cardiovascular diseases. This is an attempt made to explain the Hridya action of Dadim according to Ayurvedic as well as modern aspect. This article spreads a hopeful array for the researchers working on cardiovascular diseases.